A comparison of scatterometer and HF radar wind direction measurements. Issue 1 (2nd January 2018) - Wyatt, Lucy R.
ABSTRACT: Scatterometer winds are increasingly being used by Meteorological Services to validate and assimilate into their forecast models and reanalyses. In this paper, ASCAT wind directions obtained in coastal regions around Australia are compared with those derived from ground-based HF radar systems. Good agreement is demonstrated at wind speeds greater than 5 m/s. At lower wind speeds, scatterometer winds are not expected to be as accurate and the HF radar is probably measuring swell rather than wind direction. Examples are presented that demonstrate the advantage for regional coastal wind and wave modelling of the higher temporal resolution available with the HF radar which enables tracking of frontal features.